2020
DOI: 10.1590/s1678-9946202062057
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of synanthropic triatomines in Piaui State, Northeastern Brazil

Abstract: This is an open-access article distributed under the terms of the Creative Commons Attribution License.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 36 publications
3
3
0
Order By: Relevance
“…In contrast, R. nasutus was found in municipalities in Sertao, with a single record of positivity in our study. This finding is consistent with previous studies demonstrating its presence in semi-arid areas and the Caatinga biome 17 , 29 .…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…In contrast, R. nasutus was found in municipalities in Sertao, with a single record of positivity in our study. This finding is consistent with previous studies demonstrating its presence in semi-arid areas and the Caatinga biome 17 , 29 .…”
Section: Discussionsupporting
confidence: 94%
“…P. lutzi was found to be spread across four mesoregions; the Metropolitan region was the only region with no records of this species. Previous studies 17 , 29 conducted in Northeastern Brazil have reported the presence of this species mainly in the semi-arid regions of the Agreste region, with its absence noted in the coastal areas; these findings are similar to our findings, and the species is still considered wild 2 , 17 . In contrast, R. nasutus was found in municipalities in Sertao, with a single record of positivity in our study.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The occurrence of native species of triatomines in the urban home environment of Montes Claros ratifies the potential for vector transmission of T. cruzi in the endemic region of northern Minas Gerais (Galvão, 2014). The presence of triatomines in urban areas has been shown in other studies carried out in Brazil (Dias, Queiroz, Diotaiuti, et al., 2016; Dias, Queiroz, Martins, et al., 2016; Ribeiro et al., 2016; Santos et al., 2020), Peru (Khatchikian et al., 2015), Mexico (Tamay‐Segovia et al., 2017) and Argentina (Gaspe et al., 2020; Provecho et al., 2021; Vallve et al., 1996) where an occurrence of T. infestans infected with T. cruzi was observed in the urban area (Provecho et al., 2021).…”
Section: Discussionmentioning
confidence: 51%